A multi-centre prospective randomised equivalence trial of a soft bandage and immediate discharge versus current treatment with rigid immobilisation for torus fractures of the distal radius in children: Protocol for the Forearm Fracture Recovery in Children Evaluation Trial (FORCE) - Achten, J; Knight, R; Dutton, S; Costa, M; Mason, J; Dritsaki, M; Appelbe, D; Messahel, S; Roland, D; Widnall, J; Perry, D (British Editorial Society of Bone and Joint Surgery, 2020)
Introduction: Torus fractures are the most common childhood fracture, accounting for 500,000 UK emergency attendances per year. UK treatment varies widely due to lack of scientific evidence. This is the protocol for a randomised controlled equivalence trial of ‘the offer of a soft bandage and immediate discharge’ versus ‘rigid immobilisation and follow-up as per the protocol of the treating centre’ in the treatment of torus fractures of the distal radius.